Effects of Eimeria challenge on growth performance, intestine integrity, and cecal microbial diversity and composition of yellow broilers - Linjie Su; Shuping Huang; Yanling Huang; Xue Bai; Runhui Zhang; Yan Lei; Xi Wang (Poultry Science)
The invasion of Eimeria causes damage to the intestinal barrier, nutrient leakage, and microbial imbalance in poultry. We aimed to investigate the effects of Eimeria infection on growth performance, intestinal integrity, and cecal microbial diversity and composition of yellow broilers. A total of 180 male yellow broilers were randomly divided into an unchallenged control and an Eimeria challenge treatment group within 18 floor pens (10 chicks/pen, 9 replicate pens/group). On day 10, 90 chicks received a cocktail of E. maxima, E. acervulina, and E. tenella oocysts (105/chick) to induce coccidial infection, and the other 90 received an aliquot of PBS. The Eimeria challenge resulted in increased bird feed consumption and FCR from day 11 to 21 (all P < 0.01). Higher fecal Eimeria counts, duodenal, jejunal, and cecal lesions were observed in the challenge group on day 12, 15, 15, 18 respectively (all P < 0.05). Furthermore, the infected birds had larger livers and small intestines, deeper villus crypt, and decreased expression of Claudin-1 on day 21 (all P < 0.05). The 16S rRNA sequencing indicated that alpha diversity (Sobs, Shannon, Simpson, Ace, or Chao) of cecal microbials was not affected by Eimeria challenge (all P > 0.05). However, the PCoA and LEfSe analyses indicated that the Eimeria challenge altered microbial distribution by decreasing the abundance of Firmicutes and enriching the abundance of Proteobacteria at the phylum level. At the genus level, Clostridia vadin BB60 and Lachnospiraceae NK4A136 group were reduced, while Escherichia-Shigella were enriched in the challenged yellow broilers (all P < 0.05). Correlation analyses demonstrated that the birds with higher Lachonospiraceae NK4A136 group and Clostridia vadin BB60, and lower Escherichia-Shigella in their cecal content gained more BW and reached a lower FCR from day 11 to 21 (all P < 0.05). In conclusion, Eimeria infection compromised feed efficiency of yellow broilers by damaging intestinal barrier and shifting cecal microbiota towards colonizers associated with poor performance. Restoring the dysbiotic microbiome could be a potential strategy for improving feed efficiency in yellow broilers under coccidial challenge.